2003
DOI: 10.1093/annonc/mdg333
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of multimodality treatment for locally advanced cervical cancer: neoadjuvant carboplatin and paclitaxel followed by radical hysterectomy and adjuvant cisplatin chemoradiation

Abstract: The triple modality of neoadjuvant chemotherapy followed by radical hysterectomy and adjuvant radiation concurrent with cisplatin is a highly active treatment for locally advanced cervical carcinoma with acceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 37 publications
6
57
3
1
Order By: Relevance
“…Table 5 shows the results of the present study in comparison to those of previous reports (Sugiyama et al, 1999;Hwang et al, 2001;Dueñas-Gonzalez et al, 2001;D'Agostino et al, 2002;Di Vagno et al, 2003;Dueñas-Gonzalez et al, 2003;Umesaki et al, 2004; and this study. Table 5.…”
Section: Discussionsupporting
confidence: 64%
“…Table 5 shows the results of the present study in comparison to those of previous reports (Sugiyama et al, 1999;Hwang et al, 2001;Dueñas-Gonzalez et al, 2001;D'Agostino et al, 2002;Di Vagno et al, 2003;Dueñas-Gonzalez et al, 2003;Umesaki et al, 2004; and this study. Table 5.…”
Section: Discussionsupporting
confidence: 64%
“…Of the patients who received neoadjuvant chemotherapy, 63-81% were treated postoperative concurrent chemoradiation. 18,31 In this study, a significantly lower proportion of patients treated with NAC received postoperative radiation (52.9% vs. 82.9%) than those undergoing PS. Despite this difference, the disease-free and overall survival rates in the two groups were not statistically different, although the NAC group had a tendency of higher 5-year disease-free survival rate than the PS group.…”
Section: Discussionmentioning
confidence: 63%
“…Moore et al (2003) reported that patients benefited from neoadjuvant chemotherapy, which led to better clinical response and operability rates. Dueñas-Gonzalez et al (2003) found that the triple modality of neoadjuvant chemotherapy followed by radical hysterectomy and adjuvant radiation concurrent with cisplatin was a highly active treatment for locally advanced cervical carcinoma. They used three 21-day courses of carboplatin (AUC 6) and paclitaxel (175 mg/m 2 ), both administered by 3-hour infusion beginning on day 1 as neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%